2019
DOI: 10.4103/jlp.jlp_139_18
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance profile and co-production of extended spectrum beta lactamases and AmpC in Acinetobacter spp. in a level 1 trauma center from India

Abstract: INTRODUCTION: Acinetobacter baumannii has now emerged as a significant nosocomial pathogen in health-care setting ESP in intensive care units. Rapidly growing resistance among clinical isolates suggests a need to detect resistance mechanisms in this organism. The present study was designed to compare the various phenotypic tests available with the gold standard of genotype. METHODOLOGY: The present study was conducted to include all isolates of Acinetobacter spp. isolated over 3 years. Their resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…They showed that about 35% of A. baumannii isolates produced AmpC and MBL enzymes [ 8 , 25 ]. However, these findings contrast with the previous studies in India and Pakistan [ 26 , 27 ]. Also, by the time A. baumannii isolates acquire resistance to β -lactams and carbapenems, they often acquire resistance to several other antimicrobial agents as well [ 26 ].…”
Section: Discussioncontrasting
confidence: 99%
“…They showed that about 35% of A. baumannii isolates produced AmpC and MBL enzymes [ 8 , 25 ]. However, these findings contrast with the previous studies in India and Pakistan [ 26 , 27 ]. Also, by the time A. baumannii isolates acquire resistance to β -lactams and carbapenems, they often acquire resistance to several other antimicrobial agents as well [ 26 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Similar rate of AmpC producers were also reported by Yadav SK et al ( 18 ) (38.5%) and Richa Hans et al ( 19 ) (56%). However Batra et al ( 15 ) has reported only 12% AmpC producers. Based on these observations it is clear that percentage of ESBLs and AmpC produced by A. baumannii varied from study to study in different geographical areas.…”
Section: Discussionmentioning
confidence: 98%
“…ESBL identification in Acinetobacter spp. is not easy as standard protocols are not available unlike in Enterobacteraceae ( 15 ). 23.4% of A. baumannii were ESBL producers in the present study and results are almost in agreement with another Indian study by Amandeep Kaur et al ( 1 ) who reported 27.5% and a study from Malaysia by Khan M et al who reported 22% ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is a serious warning, as β -lactamases pose a significant threat to the effectiveness of antibiotics currently available for medical use. Other literature resources have also shown that β -lactamases are important in the emergence of antimicrobial-resistant strains and have reported a large increase in resistance among A. baumannii strains in healthcare settings [ 28 , 29 ]. Thus, due to such a high prevalence of resistance, antibiotics must be used judiciously by clinicians, and appropriate infection control measures need to be implemented to control the spread of infections in hospitals.…”
Section: Discussionmentioning
confidence: 99%